2021
DOI: 10.3390/microorganisms9061273
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation with Mycorrhizal Fungi and Irrigation Management Shape the Bacterial and Fungal Communities and Networks in Vineyard Soils

Abstract: Vineyard-living microbiota affect grapevine health and adaptation to changing environments and determine the biological quality of soils that strongly influence wine quality. However, their abundance and interactions may be affected by vineyard management. The present study was conducted to assess whether the vineyard soil microbiome was altered by the use of biostimulants (arbuscular mycorrhizal fungi (AMF) inoculation vs. non-inoculated) and/or irrigation management (fully irrigated vs. half irrigated). Bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 84 publications
2
6
0
Order By: Relevance
“…In any case, the PCoA results can also prove these affinity relationships (Figure S3). Similarly, many studies on soil ecosystems also confirmed that bacteria are sensitive to soil type [5,36], and fungi are sensitive to irrigation pattern [11,37]. Moreover, Proteobacteria, Actinobacteria, and Acidobacteria were essential members for the bacterial phyla (Figure 2A), which is consistent with previous studies on soil [7,38].…”
Section: Discussionsupporting
confidence: 89%
“…In any case, the PCoA results can also prove these affinity relationships (Figure S3). Similarly, many studies on soil ecosystems also confirmed that bacteria are sensitive to soil type [5,36], and fungi are sensitive to irrigation pattern [11,37]. Moreover, Proteobacteria, Actinobacteria, and Acidobacteria were essential members for the bacterial phyla (Figure 2A), which is consistent with previous studies on soil [7,38].…”
Section: Discussionsupporting
confidence: 89%
“…Both hypoxia and high ammonia can stress the soil microbes, leading to more positive links. (2) Many studies ( Kong et al, 2019 ; Torres, Yu & Kurtural, 2021 ) have shown that microbial inoculation could increase the positive interaction of microbial network. Microorganisms originating from the addition of manure could also enhance the association of microorganisms ( Yang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The inoculation of beneficial organisms in vineyards offers a promising method for SOM enhancement. Particularly, mycorrhizal fungi improve the relationships between vines and soil [146] with enhancing consequences on photosynthetic activity and C assimilation [147]. The allocation of vine photosynthates to the mycorrhizae, as well as their dampening of the rhizosphere-priming effect on SOM decomposition, might additionally contribute to higher SOM levels in vineyards [148].…”
Section: Dynamics Of Winegrowing Systems and Levels Of Soil Organic M...mentioning
confidence: 99%